PERPUSTAKAAN UMUM REKREATIF DI BANJARBARU - Marhadi, Marhadi; Dahliani, Dahliani (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
The design of a Recreative Public Library in Banjarbaru is motivated by the low interest in the reading culture of the community, especially in the millennial generation and the need for new places and facilities in the library that can accommodate various activities, especially in terms of sharing, discussing, relaxing, educating and recreational (Edutainment) and other activities aligned with the public library. Through the concept of Edutainment, the design of the Recreative Public Library can be a forum for developing and increasing interest in the reading culture of the community as well as being an additional facility for edutainment activities in accordance with the context of "the pleasure of reading" by using the symbiosis method and a recreational architectural approach which can highlight the function of the library as education but also as a place of recreation, besides that it can also reinterpret the user's view of library design in a more modern era.